Rab GTPases: The Key Players in the Molecular Pathway of Parkinson’s Disease - Shi, Meng-meng; Shi, Chang-he; Xu, Yu-ming (Frontiers in Cellular Neuroscience, 2017)
Parkinson’s disease (PD) is a progressive movement disorder with multiple non-motor symptoms. Although family genetic mutations only account for a small proportion of the cases, these mutations have provided several lines of evidence for the pathogenesis of PD, such as mitochondrial dysfunction, protein misfolding and aggregation, and the impaired autophagy-lysosome system. Recently, vesicle trafficking defect has emerged as a potential pathogenesis underlying this disease. Rab GTPases, serving as the core regulators of cellular membrane dynamics, may play an important role in the molecular pathway of PD through the complex interplay with numerous factors and PD-related genes. This might shed new light on the potential therapeutic strategies. In this review, we emphasize the important role of Rab GTPases in vesicle trafficking and summarize the interactions between Rab GTPases and different PD-related genes.